On the Challenges of Transnational Feminist Translation Studies - Flotow, Luise (TTR)

(untitled) (Association canadienne de traductologie, 2017)
The term “transnational” developed over the 20th century to describe cosmopolitan, multicultural societies that stem from migration; the concept of transnational feminist translation studies adds references to postcolonial feminisms to this term, offering new collaborative avenues of research and publication. This article reports on the challenges such collaborations pose, and how they have impacted an early attempt to produce an anthology of scholarly texts in the area of transnational feminist translation studies (Flotow and Farahzad, 2017). It develops a number of specific areas of difficulty: the “hegemony” of English in academic publishing and how this affects the circulation of feminist texts from beyond the Anglo-American Eurozone; the issue of power relations between editors and authors, cultures, and languages; questions of inclusion and exclusion, especially as different religious/cultural backgrounds affect scholarly discussion; and the importance of women’s/feminist diversity as well as the risks/benefits of a universalizing discourse. While the article is concerned with “challenges”, it ends with a call for more such collaborative transnational work to re-energize and promote the field of feminist translation studies worldwide.